A QUALITATIVE RESEARCH ON THE UNEMPLOYMENT EXPERIENCES OF GRADUATES OF SPORT SCIENCES FACULTIES - ŞAŞMAZ ATAÇOCUĞU, Muazzez; KEREM ZELYURT, Mert (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2017)
Unemployment has been recognized as an important indicator of economies of the countries. Unemployment which expresses the status of complete unavailability of "labor" as the main factor of production, is a multidimensional problem, which can be encountered in all countries from less developed countries to developed countries. It is emerging in all sectors with various proportions and features. The research question of this paper was created by issues in the context of unemployment of graduates of the faculties of sports sciences which are raising labor supply to sports sector which is growing with every passing day. In the study, it was intended to analyze the unemployment experiences of faculty of sports sciences graduates (former words, the "PES") and to put the variables about the causes and consequences of this experience forward. In this context, the study sample was selected from people who were graduated from 4 separate departments of relevant faculties and have experienced unemployment. The sample consists of 20 participants for a total, 7 Physical Education and Sports Teaching Department, 5 Sports Management Department, 4 Coaching Education Department, 4 Recreation Department graduates. In the study, "Semi-structured in-depth interview" which is a specific research technique peculiar to "Qualitative Method" was applied. Interviews were recorded on a voice recorder, transferred to the "Word" text. Related findings (text) subjected to content analysis, were classified under 5 themes that reflect the primary problematics relevant to the subject: 1. Unemployment Duration and Job Search Practices of Graduates, 2. The Perception of Employment in Anatolian Cities, 3. Pedagogic Formation Certificate as a Business Opportunity, 4. Effective Elements in Finding a Job, 5. The Perception of the Profession. From the results of the research, in general, the following tips were obtained: It appeared that those who have graduated from various departments of Faculties of Sports Sciences were exposed to a long duration of unemployment, finally they have to work outside of the department they have graduated or a completely different sector; legal regulations related the departments they graduated (pedagogic formation education), lack of sport facilities and materials in the city they live, issue of torpedo (nepotism), fewer job opportunities in the public sector, as well as precariousness of work in the private sector which offers various job opportunities play a role on unemployment of graduates.